A Review on Methods to Find Harmonic Sources in IEEE Buses - Sumiran Gupta; R.S. Mandloi; Dr. Sandeep Bhongade (International Journal of Engineering and Management Research, 2022)
This Paper Gives A Comprehensive Evaluation Of Approaches For Suppressing Harmonics In Ieee Buses By Detecting Harmonics In The Buses Using Various Methodologies, Accounting For A Variety Of Uncertainties, And Then Determining The Right Source Of Harmonics. Matlab Software To Determine And Test Both The Problem And The Solution Utilizing Various Methods. Increased Use Of Nonlinear Loads Causes Sag And Swell Due To Multiple Times Switching, Which Has An Impact On Power Quality (Pq) And Raises The Demand For Power Quality Enhancement. Various Forms Of Irregularities Are Connected With Power System Signals, Resulting In Harmonics Of Various Frequencies [26] Therefore, There Is A Pressing Demand For Approaches Right Now That Can Influence The Present Era's Collective Harmonic Impact On Various Modern Loads [25].